Assessment of Heavy Metal Contamination in Liver, Gizzard, and Brain of Parent, Broiler, Layer, and Domestic Poultry Chickens in Dhaka, Bangladesh: A Threat to Bangladeshi Chicken Consumers - Sakhawat Hossain; Fayaz Bin Farid; Md. Nahid Bin Hasan; S.M. Abidur Rahman; Md. Ali Muztaba; Md. Mizanur Rahman (CV. Literasi Indonesia, 2022)
The presence of heavy metals in poultry chicken which climbs up to the body through the regular food chain is a matter of prime concern for health safety issues. A total of five types of chicken were collected from Kaptan Bazar, Gulistan, Dhaka, and three samples from each namely liver, gizzard, and brain were analyzed by using AAS (Atomic Absorption Spectrophotometer) to detect the concentration of heavy metals which are Cadmium (Cd), Chromium (Cr), Lead (Pb) and Zinc(Zn). The founding concentration are (2.486,2.490 and 2.493), (0.998,1.497 and 1.689), (2.498,0.998 and 0.999), (2.497,0.998 and 0.998), (0.999,1.495 and 1.781) mg/kg for Cd, (3.381,1.544 and 1.096), (1.048,2.245 and 1.746), (2.340,4.732 and 2.498), (0.499,0.848 and 2.495), (1.999,1.395 and 0.950) mg/kg for Cr,(7.458, 7.931 and 7.977), (5.190,10.479 and 9.008), (13.443,8.982 and 8.548), (2.397,6.483 and 4.141), (1.849,1.198 and 1.306) mg/kg for Pb and (32.430,49.810 and 58.421), (348.52, 474.051 and 619.648), (BDL), (153.476, 98.528 and 149.700), (68.267,74.775 and 53.778) mg/kg for Zn in the liver, gizzard and brain of parent, broiler, layer, domestic and cockerel chicken respectively. All the concentration found in the sample exceeds the recommended value set by WHO/FAO. A precautionary measure should be taken for proper waste management and public awareness need to be raised to resist the exposure of heavy metal from an industrial zone to the open place.